Clinico-pathological Consistency in Diagnoses of Skin Diseases: A Retrospective Multi – Center Study in Western Afghanistan - Barakzaie, Bashir A.; Saraj, Wazir A.; Noorzaie, Tamana; Timori, Shabana; Alimi, Sid Naiem; Sadat, Nabila; Yousofzaie, Muhammad Reza; Kazimi, Maryam; Bromand, Haneye; Rahimi, Fariba; et al. (British Journal of Healthcare and Medical Research, 2025)
Background: The pathological reports of two centers in Herat City- Afghanistan, the dermatology department of Herat Regional Public Hospital and Barakzaie Dermatology and aesthetic center, under the technical support of MBC center, Turin University- Italy and organization of Jami Medical Faculty, Herat- Afghanistan, is analyzed to find out the consistency between clinical and laboratory diagnoses. The reports are generated by Pzhohish Histopathology Laboratory located in Mashhad Iran where the specimens from the two mentioned centers are sent for the diagnosis. Materials and Method: This study includes the total of 177 reports, 70 from the hospital and 107 from Barakzaie Dermatology and aesthetic Center which were obtained for a period of 1.5 years. The specimens were either from skin or from the mucosal site or from the blood serum. Each report includes 3 clinical impressions and one or rarely more than one pathological diagnoses. EPI Info 7 was used as a mean for data analyses. Level of significance was set as at p<0.05. Results: 86(49%) patients were male and 91 (51%) were female with almost equal ratio of male to female Patients aged ranged from 1 to 100 years with a mean age of 43.7 year (sd=23). Age category 40 -60 was in the top 30.9% (n=55) while age over 100 was the lowest 2.2% (n=4). The overall consistency rate was 70% (n=125), and 30% inconsistent with clinical impression (n=52). 66 female and 59 male reports were consistent with clinical impression while 25 female and 27 male cases were inconsistent with the clinical impressions, this finding was not significant statically (p=0.6). 110 confirmed and 15 descriptive reports were consistent with the pathology report (70%), while 29 confirmed and 23 descriptive reports were inconsistent with the clinical impression (30%) confirmed laboratory reports were more consistent with the clinical impressions and this was significant statically (p=0.0000. Conclusion: Even though, skin biopsy is a gold standard and only confirmatory test for some of the skin disorders, inaccessibility to specialized laboratory services in our country is a big challenge against dermatologist, minimizing the chance of performing enough and necessary lab investigation.